A Formação ética, moral e em valores na pesquisa em educação - Silva, Matheus Estevão Ferreira da (Editora Oficina Universitária, 2022)
This collection came up with the proposal to disseminate research results, developed within the scope of the Graduate Program in Education (PPGE) of the Faculty of Philosophy and Sciences (FFC), São Paulo State University "Júlio de Mesquita Filho" (UNESP), Campus by Marília, which address the intersection of ethics, morals and values with Education. The book brought together 18 texts resulting from Master's, Doctorate and Post-Doctoral research, completed or in progress, which were distributed in two parts. In the first part, Contributions, analyzes and theoretical reflections, there are 11 texts that approach research results that investigated the themes in question from a theoretical point of view. In the second part, Diagnostics, interventions and reviews of empirical research, 08 texts resulting from empirical research or from reviews of the production of these investigations. 15 of these texts are authored by students, who may or may not have the co-authorship of their respective advisors, while the other 03 texts are authored by invited professors, in some way were also involved with the PPGE. This gathering of texts resulted in a book that deals with some of the main topics of research in Education on the issues in question, its current advances, challenges and future perspectives.